A Strategic Analysis of Impact of the WTO Accession on China's Telecommunication Industry - Zhang, Lei (2007)
Overall this study will research the impact of China's accession to the WTO on China's telecommunication industry. First of all, it is going to analyze the external and internal of China's Telecommunication Industry using PEST and Five Forces analysis separately. Secondly it is mainly going to analyze the opening of China's Telecommunication market before and after WTO Accession. Thirdly the main body of this work is the strategic analysis of China's Telecommunication Industry. In the analysis of the China Telecom operators, it will research the advantages and disadvantages of China's Telecommunication Industry Operators. Based on the analysis, the recommendations for the Development of China's Telecommunication Industry are therefore given by suggesting making strategic alliance to create sustainable competitive advantage for China Telecommunication Companies.